A spatial analysis of border “security” and jaguars in the U.S.-Mexico borderlands - Hausermann, Heidi; Hutchinson, Eliot; Walder-Hoge, Zoey (Frontiers in Conservation Science, 2024)
a jaguar (Panthera onca) named Border King was seen in Arizona's Peloncillo Mountains, followed by a sighting of a second male, Macho B, in September. The cats had crossed the U.S.-Mexico border and quickly came to symbolize a conservation success story in complicated geopolitical terrain. Two decades later, the Trump Administration's increased militarization of the borderlands prompted concerns about the deleterious impacts of border wall expansion for jaguar movement and survival. This study examines the expansion of border barriers, and potential impact on jaguar habitat. Using geospatial technologies and public data, we measure border barrier expansion between 2005 and 2021. We found that of the suitable jaguar habitat that touched the border in the study area (155 km), 86% (or 133 km) had been cut off by border barrier by 2021. We distinguish "wall" from other barriers, including vehicle barriers, using aerial imagery. Our results show although barriers built from 2006 to 2015 were triple the length of those built under Trump, the majority consisted of vehicle barriers, which animals may be able to cross. Trump era construction shifted vehicle barriers to restrictive walls limiting animal movement. We argue examining the type of barrier is crucial in understanding the potential for border "security" disruption to jaguar movement and futures in the borderlands.